Češka in slovaška literarna komparativistika - stanje in dosežki - Zelenka, Miloš (Primerjalna književnost, 2005)
The Czech and Slovak schools of comparative literary studies were formed in interwar Czechoslovakia. The comparative method was cultivated - apart from the older positivist generation (Murko, Polívka, and others) - especially by Wollman (with his comparative literary morphology) and Wellek who linked Prague structuralism, German neo-idealism and Ingarden's phenomenology. Slovak comparative studies (M. Bakos, D. Ďurisin, P. Koprda) moved from genetic-contactological comparative studies towards typology. Contemporary Czech and Slovak comparative studies focus on socio-political and cultural research, while preserving a philological approach to concrete texts. They also elaborate a theory of world (univesal) literature and interliterariness.
Keywords: Wollman, Frank, 1888-1969; Wellek, René, 1903-1995; Ďurišin, Dionýz, 1929-1997; comparative literature; primerjalna književnost; literarna teorija; literary theory; Czech Republic; Češka; Slovaška